2011
DOI: 10.1111/j.1757-1707.2011.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest management on the carbon dioxide emissions of wood energy in integrated production of timber and energy biomass

Abstract: The aim of this work was to study the sensitivity of carbon dioxide (CO 2 ) emissions from wood energy to different forest management regimes when aiming at an integrated production of timber and energy biomass. For this purpose, the production of timber and energy biomass in Norway spruce [Picea abies (L.) Karst] and Scots pine (Pinus sylvestris L.) stands was simulated using an ecosystem model (SIMA) on sites of varying fertility under different management regimes, including various thinning and fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 38 publications
5
53
0
Order By: Relevance
“…The performance of SIMA model has been reported earlier and the simulated growth and the measured mean annual [49]. In addition, the simulations have found a good agreement with the empirical growth and yield model Motti [50] in the simulations of volume growth of managed Norway spruce (Picea abies L. Karst) and Scots pine (Pinus sylvestris L.) stands in 13 different locations from southern to northern Finland on medium fertile sites over an 80-year rotation period [16].…”
Section: Sima Ecosystem Modelsupporting
confidence: 58%
See 1 more Smart Citation
“…The performance of SIMA model has been reported earlier and the simulated growth and the measured mean annual [49]. In addition, the simulations have found a good agreement with the empirical growth and yield model Motti [50] in the simulations of volume growth of managed Norway spruce (Picea abies L. Karst) and Scots pine (Pinus sylvestris L.) stands in 13 different locations from southern to northern Finland on medium fertile sites over an 80-year rotation period [16].…”
Section: Sima Ecosystem Modelsupporting
confidence: 58%
“…Current Finnish forest management recommendations aim mainly at timber (sawlogs and pulpwood) production and there may be a need to modify these if both carbon sequestration and production of timber and energy biomass are aimed to be increased to promote emission mitigation (e.g., Matala et al [15]; Routa et al [16]). Carbon sequestration into forests can be increased by using less intensive thinnings and higher stocking over a rotation period, but this may decrease the economic profitability of the production due to a delay in harvesting (e.g., Pyörälä et al [17]).…”
Section: Introductionmentioning
confidence: 99%
“…The model comparison by Routa et al [35] also indicated good agreement between simulations using the gap-type forest ecosystem model SIMA and the empirical growth and yield model MOTTI [32] for the mean annual volume growth, with and without N fertilization, of managed Norway spruce and Scots pine stands on medium fertile upland forest sites.…”
Section: Outlines Of Forest Ecosystem Model Used Simulationsmentioning
confidence: 94%
“…In all three regions, the study was limited to Norway spruce (Picea abies). The harvest of aboveground energy biomass is generally integrated with the harvest of timber in conventional forestry in Sweden [29], and therefore the release of GHG and energy consumed prior to and during final felling were allocated to the production of timber. The management practices and technologies used were assumed to be constant during the whole lifespan of the forest and no improvements were considered.…”
Section: System Boundariesmentioning
confidence: 99%